Avaliação da interação das proteínas do ovo (ovalbumina e outras) com os antibióticos tetraciclina, oxitetraciclina e clorotetraciclina empregando técnicas espectroscópicas e eletroforese - Dantas, Maria Dayanne de Araújo (2015)
The albumin is the major protein from egg white, being widely used in the food, mainly in nutritional supplementation and in different food composition. Tetracyclines are a class of antibiotics broad spectrum employed in animal husbandry and poultry production. However, its abundant use and indiscriminate may result in the presence of residues this medicine in foods like egg causing toxic effects, in addition the possibility of allergic reactions. The aim of this work was evaluation interaction between ovalbumin (commercial and in natura) with tetracycline, oxitetracycline and chlortetracycline employing molecular fluorescence, molecular absorption and electrophoresis. Through the results obtained by fluorescence were calculated Stern-Volmer´s constant, biding, binding sites number between the three tetracyclines and ovalbumin, finally, the thermodynamic parameters (ΔG, ΔH and ΔS) under different conditions of pH. Kb values for TC variety from 2.11 (± 0.21) to 25.8 (± 0.30) x104 L mol-1 for OTC variety from 3.96 (± 0.07) to 58.4 (± 0.50) x104 L mol-1. And finally, the values for CTC variety from 2.45 (± 0.13) to 32.4 (± 0.40) x104 L mol-1. Depending on the pH of the resource. The number of the binding sites in all conditions was close to unity. The interaction mechanism was studied and the experimental results showed that interaction process between ovalbumin and differents tetracyclines occurred by static quenching with non-fluorescent complexes formation. The thermodynamics parameters calculated indicated that interactions occur spontaneously (ΔG < 0), and bonding forces predominant are hydrogen bonds, Van der Waals force and electrostatic interactions, depending on the pH of the resource. From the studies by synchronous fluorescence was observed shift to the tyrosine residues only pH 7.4 independent of tetracycline and ovalbumin source. For tryptophan residues were observed shift in all values of pH independent of ligand and source of ovalbumin. Through the studies by 3D fluorescence was observed decreased the fluorescence intensity of peaks 2 e 3 for commercial and egg white proteins independent of tetracycline added. From studies by FRET was possible to calculate the intermolecular distances between ovalbumin and three tetracycline studied under different conditions of pH, variety from 2.95 to 3.52 nm. With competition studies was observed there was competition for ovalbumin binding site only by ion Mg (II) and TC. For OTC, there was competition for the binding site of the protein among all ions evaluated. Finally, for CTC, the addition of ions Ca (II), Mg (II) e Cu (II) caused competition between these ions and CTC by protein. Through UV-Vis studies, there was the formation of complexes between ovalbumin and distintic tetracyclines evaluated in this work, independent of pH and source. From electrophoresis studies was observed shift of the protein band for the native protein (indicating increase electrophoretic mobility) due to the presence of the ligands. The nuclear magnetic resonance of hydrogen (1H NMR) studies indicated that signals of all hydrogens tetracycline molecule had shift and enlargement and the relaxation time (T1) decreasing in the presence of the ovalbumin.